Determinasi Keberhasilan Digital Internationalization UMKM melalui Platform Economy Berbasis E-Commerce di Banyuwangi: Perspektif Resource-Based View (RBV) - wardha Nilawati; Sudarmiatin; Heri Pratikto (GREENOMIKA, 2026)
This study aims to identify the determining factors of SME digital internationalization success through e-commerce-based platform economy in Banyuwangi, East Java, employing the Resource-Based View (RBV) framework as the primary theoretical foundation to understand how SMEs' internal resources and capabilities become determinants of competitive advantage in international digital markets. The study adopts a Constructivist Grounded Theory paradigm (Charmaz, 2014) with an iterative-cyclical design. A total of 25 participants were selected through theoretical sampling, comprising eight digitally export-successful SMEs, nine transitional SMEs, and eight SMEs that had not yet achieved success. Data were collected through semi-structured in-depth interviews, participatory observation, and document analysis, then coded using NVivo across three stages: initial, focused, and selective coding. The findings produced a core category of Layered Digital Trust Building, illustrating that SME brand equity within digital platform ecosystems is constructed incrementally through the accumulation of trust signals at every point of interaction — from product visual presentation and local brand narratives to service responsiveness and review management. Consistent with the RBV perspective, adaptive digital capabilities, local brand narratives, and seller community social capital were proven to be valuable, rare, and difficult-to-imitate resources (VRIN) that distinguish successful SMEs from those yet to succeed. These findings are conceptualized in the Digital Trust Escalation Model, encompassing four stages: digital presence, social proof, authentic narrative, and brand independence. The study concludes that platform economy merely provides infrastructure; success is determined by the adaptive digital capabilities and trust strategies developed by business actors. This study aims to identify the determining factors of SME digital internationalization success through e-commerce-based platform economy in Banyuwangi, East Java, employing the Resource-Based View (RBV) framework as the primary theoretical foundation to understand how SMEs' internal resources and capabilities become determinants of competitive advantage in international digital markets. The study adopts a Constructivist Grounded Theory paradigm (Charmaz, 2014) with an iterative-cyclical design. A total of 25 participants were selected through theoretical sampling, comprising eight digitally export-successful SMEs, nine transitional SMEs, and eight SMEs that had not yet achieved success. Data were collected through semi-structured in-depth interviews, participatory observation, and document analysis, then coded using NVivo across three stages: initial, focused, and selective coding. The findings produced a core category of Layered Digital Trust Building, illustrating that SME brand equity within digital platform ecosystems is constructed incrementally through the accumulation of trust signals at every point of interaction — from product visual presentation and local brand narratives to service responsiveness and review management. Consistent with the RBV perspective, adaptive digital capabilities, local brand narratives, and seller community social capital were proven to be valuable, rare, and difficult-to-imitate resources (VRIN) that distinguish successful SMEs from those yet to succeed. These findings are conceptualized in the Digital Trust Escalation Model, encompassing four stages: digital presence, social proof, authentic narrative, and brand independence. The study concludes that platform economy merely provides infrastructure; success is determined by the adaptive digital capabilities and trust strategies developed by business actors.